Exploring the public perception of Communist Heritage in Post-communist Albania - Iacono, Francesco; Këlliçi, Klejd L. (Ex Novo: Journal of Archaeology, 2016)
More than a quarter of a century after the fall of the eastern bloc (broadly intended), former communist countries have dramatically changed. Yet the memory of the recent past is sometimes perceived as being accompanied by a considerable sense of unease. This process is mirrored clearly in the way some countries have dealt with the physical remains of the regime. This paper will focus on a case study from contemporary Albania and represents one of the first attempts at addressing the social significance of the remnants of the recent communist past in this country. It is undertaken not only through a theoretical and historical investigation, but also via a direct survey of the public (in this case a sample of citizens of the capital city Tirana). Our results suggest that, contrary to our initial assumptions, there is a considerable widely shared interest in the material remnants of the regime and that its cultural heritage its cultural heritage still needs to be explained.